2022
DOI: 10.1371/journal.pone.0271212
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices [KAP] toward COVID-19: A cross-sectional study in the New York Metropolitan Area and California Bay Area

Abstract: Objective The 2019 novel coronavirus [COVID-19] pandemic has necessitated the implementation of public health initiatives [PHI] to slow viral spread. We evaluated the effectiveness of PHI through a survey of COVID-19 knowledge, attitudes and practices [KAP]. Methods This cross-sectional study was conducted primarily during stay-at-home orders in New York and San Francisco. A volunteer sample of 675 U.S. participants completed a KAP questionnaire after electronic distribution. Results Participants had good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Willingness to take antivirals given a positive test was associated with being boosted or double boosted among 50-54 years, and those with immunosuppression or disability, findings similar to the characteristics associated with knowledge and attitudes toward antivirals. [10] Other socioeconomic factors indicating higher level of resources, consistent with the factors associated with knowledge and attitude, were also associated with willingness to take antivirals, such as working full time, owning a home, and education. Except among those older than 65 years, being fully vaccinated or boosted were also associated with being willing to take an antiviral if a doctor recommended it in each group.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Willingness to take antivirals given a positive test was associated with being boosted or double boosted among 50-54 years, and those with immunosuppression or disability, findings similar to the characteristics associated with knowledge and attitudes toward antivirals. [10] Other socioeconomic factors indicating higher level of resources, consistent with the factors associated with knowledge and attitude, were also associated with willingness to take antivirals, such as working full time, owning a home, and education. Except among those older than 65 years, being fully vaccinated or boosted were also associated with being willing to take an antiviral if a doctor recommended it in each group.…”
Section: Discussionmentioning
confidence: 76%
“…Understanding psycho-social determinants of health such as knowledge, attitudes, and perceptions (KAPs) have proven useful in identifying potential underlying misconceptions and barriers hindering patient uptake of treatment, and in shaping targeted strategies for successful adoption and subsequently improved management of diseases. [10, 11] If knowledge about COVID-19 antivirals among those eligible is low, their full benefit may not be realized. [12] As such it is important to assess the underlying gaps in public knowledge, attitudes, and perceptions to better understand and identify opportunities and methods to improve antiviral uptake.…”
Section: Background and Introductionmentioning
confidence: 99%
“…Caregivers were aimed to make up 78% of the sample; administrative staff were to comprise 12% of the sample, and environmental health workers were planned to account for 10% of the sample size. This sample was collected via volunteer purposive sampling, similar to another KAP study [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“… Nam (2023) showed that digital empowerment of older adults significantly affects their COVID-related knowledge and behavior scores. Moreover, Mark, Udod, Skinner, and Jones (2022) highlighted the need for enhanced educational resources aimed at underprivileged populations and communities, especially among less-educated groups that display lower levels of COVID-19 knowledge. The KAB model, proposed by Bettinghaus (1986) , is a systematic investigation of health empowerment.…”
Section: Conceptual Frameworkmentioning
confidence: 99%